Study of anxiolytic and motor co-ordination activity of Cucurbita moschata and its possible mechanism through GABA receptors. (June 2020) - Arora, Indu; Behl, Tapan; Grover, Madhuri; Sachdeva, Monika; Pal, Giridhari; Khan, Nadeem
Abstract: Purpose: To evaluate anxiolytic and motor coordination activity of ethanolic and ethyl acetate extracts of Cucurbita moschata seeds (CM) in mice. Method: Seeds were dried, powdered and extracted in two different solvents, one is ethanol and other is ethyl acetate. The extracts were orally administered in mice for fourteen days followed by testing in Elevated plus Maze (EPM) and Light Dark Box (LDB) for studying the anxiolytic behaviour and the rota rod was used to check the motor coordination behaviour. Result: Both extracts showed prominent anxiolytic activity but ethanolic extract of Cucurbita moschata seeds (EECM) (200 mg/kg) showed best result which was comparable to standard drug Alprazolam in both the models. Moreover, an alteration was seen in motor coordination by the ethanolic extract at a dose of 200 mg/kg in contrast to group I mice. The mechanism was explored using Flumazenil drug, which proposed that the extract may increase chloride ion influx that was blocked by co-administration of negative allosteric modulator, flumazenil, suggesting a GABAA receptor mediated mechanism of action. Conclusion: Taken altogether, the present study demonstrates that both the extracts of Cucurbita moschata has shown a good anxiolytic & motor coordination activity proving the proposed study as factual. Highlights: Cucurbita moschata has shown anxiolytic activity. Cucurbita moschata has shown motor coordination activity. Cucurbita moschata plays its effect through modulation with GABA receptors.